2009
DOI: 10.1038/ng.472
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in a Chinese Han population identifies nine new susceptibility loci for systemic lupus erythematosus

Abstract: We performed a genome-wide association study (GWAS) of systemic lupus erythematosus (SLE) in a Chinese Han population by genotyping 1,047 cases and 1,205 controls using Illumina Human610-Quad BeadChips and replicating 78 SNPs in two additional cohorts (3,152 cases and 7,050 controls). We identified nine new susceptibility loci (ETS1, IKZF1, RASGRP3, SLC15A4, TNIP1, 7q11.23, 10q11.22, 11q23.3 and 16p11.2; 1.77 x 10(-25) < or = P(combined) < or = 2.77 x 10(-8)) and confirmed seven previously reported loci (BLK, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
726
3
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 856 publications
(775 citation statements)
references
References 28 publications
37
726
3
3
Order By: Relevance
“…Recently reported SLE susceptibility genes, which have yet to be replicated in Japanese such as TNFSF4 4,5,37 were not included. For the same reason, we did not include the multiple SNPs in the HLA region, which were shown to be independently associated with SLE in other populations.…”
Section: Association Between Cumulative Risk Allele Number and Clinicmentioning
confidence: 99%
“…Recently reported SLE susceptibility genes, which have yet to be replicated in Japanese such as TNFSF4 4,5,37 were not included. For the same reason, we did not include the multiple SNPs in the HLA region, which were shown to be independently associated with SLE in other populations.…”
Section: Association Between Cumulative Risk Allele Number and Clinicmentioning
confidence: 99%
“…2 In China, SLE is a major public health problem with a prevalence of 31 to 70 cases per 100 000 people. 3,4 This disease has a huge impact on quality of life due to side effects of the currently available therapies and a significantly increased risk of developing cardiovascular diseases, certain types of cancer and many other kinds of diseases. [5][6][7][8][9] However, the precise etiology of SLE remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies suggest an essential role of Aiolos at later stages of B cell differentiation (61,63). Numerous studies have identified polymorphisms in IKZF1 and IKZF3 to be associated with a risk for development of SLE (64)(65)(66)(67)(68)(69)(70)(71). Thus, modulation of Aiolos and Ikaros expression has the potential to correct multiple aspects of the immune dysregulation mediated by B cells and differentiation into autoantibody-secreting cells associated with SLE.…”
mentioning
confidence: 99%